2006
DOI: 10.1164/rccm.200507-1057oc
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Survival of Oxygen-dependent Patients with Chronic Obstructive Pulmonary Disease

Abstract: Among patients with COPD on LTOT, women were more likely to die than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 56 publications
0
50
2
5
Order By: Relevance
“…Oxygen prescriptions (duration and flow) should be based on arterial blood gas measurements and 6 minute walk tests results [80] . Longer term exposure to oxygen therapy (> 15 hr/day) over a number of years significantly improves survival [81,82] . Although oxygen therapy prescription during exercise is not well supported by evidence, in current practice, oxygen during exercise is being prescribed for individuals with severe COPD who become hypoxemic only when exercising.…”
Section: Oxygen Therapymentioning
confidence: 99%
“…Oxygen prescriptions (duration and flow) should be based on arterial blood gas measurements and 6 minute walk tests results [80] . Longer term exposure to oxygen therapy (> 15 hr/day) over a number of years significantly improves survival [81,82] . Although oxygen therapy prescription during exercise is not well supported by evidence, in current practice, oxygen during exercise is being prescribed for individuals with severe COPD who become hypoxemic only when exercising.…”
Section: Oxygen Therapymentioning
confidence: 99%
“…Gender differences: These differences for COPD survival prognosis have been reported repeatedly but remain controversial 8,[31][32][33] . Some have reported that women have better survival 8,31,32 , but others describe contradictory findings 33 .…”
Section: Components Of Copd Prognostic Scorementioning
confidence: 99%
“…Some have reported that women have better survival 8,31,32 , but others describe contradictory findings 33 . We hypothesize that it is difficult to adjust all coverable parameters in multiple-variable analysis when comparing both sexes because the two sexes have different FEV 1 predicting formulas and different reference values for exercise tolerance tests.…”
Section: Components Of Copd Prognostic Scorementioning
confidence: 99%
“…In this study, we report the role of the nmMLCK2 splice variant in vascular barrier regulation, and we describe the consequences of overexpressing this isoform specifically in murine endothelium. Furthermore, as several acute and chronic inflammatory pulmonary disorders, which include ALI and acute respiratory distress syndrome (ARDS), are influenced by gender, [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ] and [ 22 ] age, [ 23 ], [ 24 ], [ 25 ], [ 26 ] and [ 27 ] or gender-age interactions, [ 28 ], [ 29 ] and [ 30 ] we designed our study to evaluate the influence of these comodifiers on postulated nmMLCK2-mediated increases in vascular paracellular transport. This is supported by findings in mice, which like humans, have varying respiratory properties that differ between sexes [ 31 ], [ 32 ] and [ 33 ] and with age, [ 34 ] and [ 35 ] information often neglected when describing a pulmonary phenotype.…”
Section: Translational Significancementioning
confidence: 99%